Efektivitas Penggunaan Aplikasi Mommy Warning Terhadap Ketepatan Waktu Kunjungan Ulang Akseptor Kontrasepsi Suntik 1 Bulan Di PMB “RB” Tahun 2024 - Ramadhani, Puteri Ahyana; Rizani, Ahmad; Rafidah, Rafidah; Zakiah, Zakiah (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2024)
Introduction: Cempaka Subdistrict was the subdistrict that had the highest dropout rate, with 661 people (18.9%) who accepted family planning. According to a previous study conducted by researchers at PMB